The Nutrient Evaluation of Fermented Rice Bran as Poultry Feed - Hardini, Dini (International Journal of Poultry Science, 2010)
This research was conducted to find out the effect of fermentation of rice bran by Aspergillus niger in term of nutrient content. Rice bran was incubated with different length of time period of incubation; 0, 24, 48 and 72h. Parameter observed included the content of dry matter, organic matter, crude protein, soluble protein, NPN (non protein nitrogen), reducing sugar and nitrogen retention. Data obtained were subjected into analysis of variance of the completely randomized design. The result showed that incubation period gave the different significant effect (p<0.01) on the content of dry matter, organic matter, crude protein, diluted protein and nitrogen retention. But there was no significant effect (p>0.05) on the crude protein. By 72h incubation time, the fermented rice bran containing the highest nutritive value.